Bright Light Therapy for MDD in Children and Adolescents: a narrative review of literature. (1st June 2022) - Vadukapuram, R.; Trivedi, C.; Mansuri, Z.; Shah, K.; Reddy, A.
Abstract : Introduction: Major Depressive Disorder (MDD) is a common mood disorder diagnosed in children and adolescents. Bright light therapy has been effective for seasonal affective disorders, however its role in the treatment of MDD is under studied. Objectives: Our objective is to evaluate if bright light therapy (BLT) is a practical approach in treating Child and Adolescents having MDD. Methods: We performed an extensive literature search using a wide range of MeSH terms in PubMed, PubMed Central and Google Scholar. We reviewed the literature for studies (published between 1983-2021) assessing the efficacy of BLT in the treatment of MDD in children and adolescents. Results: The final search results yielded 8 randomized clinical trials and 1 case report from 1983 to 2021. BLT showed a superior effect in children and adolescents with MDD compared to the control group in the majority of the randomized trials and a case report. In six studies BLT showed good effect, however in a study by Magnusson et al. and Sonis et al., found a milder degree of improvement in depression symptoms when compared to the control group. In the majority of the studies, patients' age range was 7 years 18 and in most of the studies, patients were not on antidepressants. Conclusions: The use of BLT in children and adolescents suffering from MDD can be a promising alternative method of biological treatment, which is effective as well as well tolerated. Future long-term studies on large sample size are necessary in this field. Disclosure: No significant relationships.